Oxidant production and SOD1 protein expression in single skeletal myofibers from Down syndrome mice - Patrick M. Cowley (Redox Biology, 2017)
Down syndrome (DS) is a genetic condition caused by the triplication of chromosome 21. Persons with DS exhibit pronounced muscle weakness, which also occurs in the Ts65Dn mouse model of DS. Oxidative stress is thought to be an underlying factor in the development of DS-related pathologies including muscle dysfunction. High-levels of oxidative stress have been attributed to triplication and elevated expression of superoxide dismutase 1 (SOD1); a gene located on chromosome 21. The elevated expression of SOD1 is postulated to increase production of hydrogen peroxide and cause oxidative injury and cell death. However, it is unknown whether SOD1 protein expression is associated with greater oxidant production in skeletal muscle from Ts65Dn mice. Thus, our objective was to assess levels of SOD1 expression and oxidant production in skeletal myofibers from the flexor digitorum brevis obtained from Ts65Dn and control mice. Measurements of oxidant production were obtained from myofibers loaded with 2′,7′-dichlorodihydrofluorescein diacetate (DCFH2-DA) in the basal state and following 15 min of stimulated unloaded contraction. Ts65Dn myofibers exhibited a significant decrease in basal DCF emissions (p < 0.05) that was associated with an approximate 3-fold increase in SOD1 (p < 0.05). DCF emissions were not affected by stimulating contraction of Ts65Dn or wild-type myofibers (p > 0.05). Myofibers from Ts65Dn mice tended to be smaller and myonuclear domain was lower (p < 0.05). In summary, myofibers from Ts65Dn mice exhibited decreased basal DCF emissions that were coupled with elevated protein expression of SOD1. Stimulated contraction in isolated myofibers did not affect DCF emissions in either group. These findings suggest the skeletal muscle dysfunction in the adult Ts65Dn mouse is not associated with skeletal muscle oxidative stress.